Development of a Multi-Station Shooting Training Model to Improve Shooting Accuracy in Youth Football Players - Agung Witualar Pangestu; Aprizal Fikri; Muslimin; Noviria Sukmawati; Susilo Nugroho; Ilona Pratiwi Hutabarat (STKIP Pasundan, 2025)
Football performance depends on technical skill and physical conditioning, with shooting ability as a key determinant of goal scoring. However, youth players often show low shooting accuracy and reduced engagement due to monotonous training. This study aimed to develop and validate a multi-station shooting training model for 15-year-old football players. A Research and Development approach using the ADDIE framework was applied, involving expert validation and field trials. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive percentages and content validity measures. Results showed that the model is valid and effective, with expert validation reaching 86.6%, small-scale trials 94.37%, and large-scale trials 90.56%. The model integrates speed, accuracy, strength, core stability, leg strength, and power, improving both shooting performance and player engagement. This study provides a practical and evidence-based training model with implications for youth football coaching and sports training methodology.